Theoretical and experimental differential cross sections for electron impact excitation of the electronic bands of furfural - Jones, D. B. (2016)
R.F.C.N. thanks CNPq (Brazil) and the Science Without Borders Programme for opportunities to study abroad. D.B.J. thanks the Australian Research Council (ARC) for financial support provided through a Discovery Early Career Research Award, while M.J.B. also thanks the ARC for their support. M.J.B. and M.C.A.L. acknowledge the Brazilian agencies CNPq and FAPEMIG. P.L.-V. acknowledges the Portuguese Foundation for Science and Technology (FCT-MEC) through Grant Nos. PTDC/FIS-ATO/1832/2012 and UIO/FIS/00068/2013. G.G. acknowledges partial financial support from the Spanish Ministry MINECO (Project No. FIS2012-31230) and the European Union COST Action No. CM1301 (CELINA). Finally, R.F.d.C., M.T.d.N.V., M.H.F.B., and M.A.P.L. acknowledge support from the Brazilian agency CNPq and M.T.d.N.V. also thanks FAPESP.